Severe community-acquired pneumonia: timely management measures in the first 24 hours. Issue 1 (December 2016) - Phua, Jason; Dean, Nathan; Guo, Qi; Kuan, Win; Lim, Hui; Lim, Tow
Abstract Mortality rates for severe community-acquired pneumonia (CAP) range from 17 to 48 % in published studies. In this review, we searched PubMed for relevant papers published between 1981 and June 2016 and relevant files. We explored how early and aggressive management measures, implemented within 24 hours of recognition of severe CAP and carried out both in the emergency department and in the ICU, decrease mortality in severe CAP. These measures begin with the use of severity assessment tools and the application of care bundles via clinical decision support tools. The bundles include early guideline-concordant antibiotics including macrolides, early haemodynamic support (lactate measurement, intravenous fluids, and vasopressors), and early respiratory support (high-flow nasal cannulae, lung-protective ventilation, prone positioning, and neuromuscular blockade for acute respiratory distress syndrome). While the proposed interventions appear straightforward, multiple barriers to their implementation exist. To successfully decrease mortality for severe CAP, early and close collaboration between emergency medicine and respiratory and critical care medicine teams is required. We propose a workflow incorporating these interventions.